1997
DOI: 10.1007/s001130050198
|View full text |Cite
|
Sign up to set email alerts
|

Quality management in the early care of patients with multiple injuries: Documentation of treatment and review of quality of care

Abstract: Quality management in early clinical care of patients with multiple injuries (description of actual process, identification of problems, implementation of quality improvement) is not possible without sufficient baseline data about the present situation of medical treatment. This study investigates whether the current documentation of treatment in the emergency room is appropriate to judge upon the quality of the process and to detect problems. In addition, a set of baseline data is presented. The performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
2
9
2
Order By: Relevance
“…Like other authors, we observed missed diagnoses in early trauma care ending with discharge from hospital [10,12,13,16,17,21,23,27,31,37]. After the ER phase with CT diagnostics and immediate data evaluation, only 3 single diagnoses (2.1 %) in 2 children (2.8 %) were missed.…”
Section: Missed Diagnosessupporting
confidence: 81%
“…Like other authors, we observed missed diagnoses in early trauma care ending with discharge from hospital [10,12,13,16,17,21,23,27,31,37]. After the ER phase with CT diagnostics and immediate data evaluation, only 3 single diagnoses (2.1 %) in 2 children (2.8 %) were missed.…”
Section: Missed Diagnosessupporting
confidence: 81%
“…Most of these did not require any specific therapy. Like many other authors, we concentrated on missed diagnoses in early trauma care ending with discharge from hospital [14][15][16][17][18][19][20][21]23]. This is why missed injuries were called ''delays in diagnosis:'' they were detected during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Enderson et al [18] reported 41 missed injuries in 26 of 399 patients (9%). Zintl et al [23] reported 44 missed diagnoses in 32% of the patients after the ER phase. They judged five missed diagnoses as unjustified and potentially life-threatening.…”
Section: Delays In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Quality management of the severely injured became the main argument to support centralization [6,7]. Another strong argument is the economic dimension.…”
Section: Discussionmentioning
confidence: 99%